Incidence and predictors of asthma exacerbations in middle-aged and older adults: the Rotterdam Study - de Roos, Emmely W. (ERJ Open Res, 2021)
AIM: The aim of this study was to investigate occurrence and determinants of asthma exacerbations in an ageing general population. METHODS: Subjects aged 45 years or above with physician-diagnosed asthma in the Rotterdam Study, a population-based prospective cohort from January 1991 to May 2018, were assessed for asthma exacerbations. Exacerbations were defined as acute episodes of worsening asthma treated with oral corticosteroids. Cox proportional hazards analysis was used to investigate risk factors for a future exacerbation. RESULTS: Out of 763 participants with asthma (mean age 61.3 years, 69.2% female), 427 (56.0%) experienced at least one exacerbation, in a mean follow-up time of 13.9 years. The mean annual exacerbation rate was 0.22. Most exacerbations occurred during winter months. Risk factors for exacerbations were a history of previous exacerbations (HR 4.25; 95% CI 3.07–5.90, p<0.001)), respiratory complaints (HR 2.18; 95% CI 1.48–3.21, p<0.001), airflow obstruction (HR 1.52; 95% CI 1.07–2.15, p=0.019), obesity (HR 1.38; 95% CI 1.01–1.87, p=0.040) and depressive symptoms (HR 1.55; 95% CI 1.05–2.29, p=0.027). Compared to those not using respiratory medication, we observed higher hazard ratios for those on short-acting β(2)-agonists (SABA, i.e. rescue medication) only (HR 3.08, 95% CI 1.61–5.90, p=0.001) than those on controller medication (HR 2.50, 95% CI 1.59–3.92, p<0.001). CONCLUSION: Many older adults with asthma suffer from at least one severe exacerbation. Previous exacerbations, use of SABA without concomitant controller medication, respiratory complaints, obesity, airway obstruction and depression are independent risk factors for exacerbations.